Prototypically American: The influence of accent and race on evaluation of job candidates - Nguyen Tuong-Vy C.; Wellman Joseph D. (Psychology of Language and Communication)
Immigrants and racial minorities continue to face hiring discrimination. The current study examined the influence of accent, race, as well as perceived Americanness on hiring evaluations. White US adults (N = 375) were randomly assigned to one of six conditions based on two factors: (a) accent (standard versus foreign) and (b) race (White, Black, and Asian). Accented speakers were perceived to be less American and were subsequently less likely to be hired. However, this effect was stronger or only emerged for White and Black candidates. The perception and evaluation of the Asian candidate were not explained by perceived Americanness. Implications for being perceived as American are discussed.